2012
DOI: 10.1186/2193-9012-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Anonymous job applications in Europe

Abstract: Numerous empirical studies find a substantial extent of discrimination in hiring decisions. Anonymous job applications have gained attention and popularity to identify and combat this form of discrimination. To test whether their intended effects result in practice, in several European countries such as Sweden, France and the Netherlands field experiments were recently conducted. Also in Germany, a large field experiment has examined the practicability and potentials of this approach. Against the background of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 20 publications
1
36
1
1
Order By: Relevance
“…Another large-scale randomized field experiment took place in Germany in early 2010 (Krause, Rinne, and Zimmermann, 2012a). The publication of a correspondence testing study for Germany (Kaas and Manger, 2012) triggered a lively public debate about discrimination in the hiring decisions of German firms.…”
Section: Technological De-biasingmentioning
confidence: 99%
“…Another large-scale randomized field experiment took place in Germany in early 2010 (Krause, Rinne, and Zimmermann, 2012a). The publication of a correspondence testing study for Germany (Kaas and Manger, 2012) triggered a lively public debate about discrimination in the hiring decisions of German firms.…”
Section: Technological De-biasingmentioning
confidence: 99%
“…They also note that the employers who recruit with anonymous application systems are able to present their corporate image positively as non-discriminatory, open-minded, and objective. Krause et al (2012) also point out that recruitment practices differ greatly between countries. Therefore the introduction and implementation of an anonymous job application system in a particular location may require anything from small modifications to large, fundamental changes to current recruitment practices.…”
mentioning
confidence: 97%
“…Similar experiments have been undertaken in Germany (Krause et al, 2012), the Netherlands (Gemeente Nijmegen, 2007) and in Sweden (Aslund and Nordstrom Skans, 2012). All of these studies found that ethnic minorities benefit from anonymity since they receive higher call-backs rates when their ethnic background cannot be detected in the CV.…”
Section: Standardising Job Applications and Anonymous Cvsmentioning
confidence: 64%
“…However, they still seem to be meeting a harder selection at the stage of the job talk and the rate of job offers received by ethnic minorities remained significantly lower and could be interpreted as a proof of discriminatory selection. Krause et al (2012) stress that although applicants with a migration background globally benefit from anonymity, there are cases where they may loose from this strategy if employers favour diversity.…”
Section: Standardising Job Applications and Anonymous Cvsmentioning
confidence: 99%